2020
DOI: 10.1038/s41423-020-0361-7
|View full text |Cite
|
Sign up to set email alerts
|

B7-H7 (HHLA2) inhibits T-cell activation and proliferation in the presence of TCR and CD28 signaling

Abstract: Modulation of T-cell responses has played a key role in treating cancers and autoimmune diseases. Therefore, understanding how different receptors on T cells impact functional outcomes is crucial. The influence of B7-H7 (HHLA2) and CD28H (TMIGD2) on T-cell activation remains controversial. Here we examined global transcriptomic changes in human T cells induced by B7-H7. Stimulation through TCR with OKT3 and B7-H7 resulted in modest fold changes in the expression of select genes; however, these fold changes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…In our experiments, HHLA2 knockdown enhanced the adhesion between HepG2 cells and the extracellular matrix in vitro. Our results are consistent with a transcriptome study [ 19 ], indicating that HHLA2 is involved in regulating intercellular adhesion between primary human T cells and the extracellular matrix. In fact, the less adhesive the tumor, the more effectively it evades immune killing, which is proposed by the “tumor growth-cell immune feedback” model.…”
Section: Discussionsupporting
confidence: 93%
“…In our experiments, HHLA2 knockdown enhanced the adhesion between HepG2 cells and the extracellular matrix in vitro. Our results are consistent with a transcriptome study [ 19 ], indicating that HHLA2 is involved in regulating intercellular adhesion between primary human T cells and the extracellular matrix. In fact, the less adhesive the tumor, the more effectively it evades immune killing, which is proposed by the “tumor growth-cell immune feedback” model.…”
Section: Discussionsupporting
confidence: 93%
“…In analogy to B7.1 and B7.2 that ligate CTLA-4 and CD28 to inhibit and stimulate T cell responses respectively, B7-H7 has been shown to ligate KIR3DL3 and CD28H to inhibit and stimulate T cell responses respectively (14). However, Rieder et al showed that the inhibitory effect of B7-H7 signalling is evident as early as 24 h after the initial stimulation (11). Nevertheless, KIR3DL3 is not expressed on resting T cells and the expression is less than 5% upon cross-linking CD3 and CD28 (14).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al reported that B7-H7 inhibit T cells proliferation and cytokine secretion (2), while Zhu et al demonstrated that B7-H7 co-stimulates T cells via its receptor CD28H (4). Following these initial report, more recent studies have also reported both inhibitory and stimulatory functions of B7-H7 (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…HHLA2, a member of the B7 family, can predict poor overall survival in several cancers, including human clear cell renal cell carcinoma and colorectal carcinoma [125]. HHLA2 can suppress T-cell activation and proliferation in the presence of TCR and CD28 signaling [126], and can do this more robustly than PD-L1 [127].…”
Section: Hhla2mentioning
confidence: 99%